Two dcm gene clusters essential for the degradation of diclofop-methyl in a microbial consortium of rhodococcus sp. JT-3 and brevundimonas sp. JT-9 - Zhang, Hui (2020)
The metabolism of widely used aryloxyphenoxypropionate herbicides has been extensively studied in microbes. However, the information on the degradation of diclofop-methyl (DCM) is limited, with no genetic and biochemical investigation reported. The consortium L1 of Rhodococcus sp. JT-3 and Brevundimonas sp. JT-9 was able to degrade DCM through a synergistic metabolism. To elaborate the molecular mechanism of DCM degradation, the metabolic pathway for DCM was first investigated. DCM was initially transformed by strain JT-3 to diclofop acid and then by strain JT-9 to 2-(4-hydroxyphenoxy) propionic acid as well as 2,4-dichlorophenol. Subsequently, the two dcm gene clusters, dcmAE and dcmB1B2CD, involved in further degradation of 2,4-dichlorophenol, were successfully cloned from strain JT-3, and the functions of each gene product were identified. DcmA, a glutathione-dependent dehalogenase, was responsible for catalyzing the reductive dehalogenation of 2,4-dichlorophenol to 4-chlorophenol, which was then converted by the two-component monooxygenase DcmB1B2 to 4-chlorocatechol as the ring cleavage substrate of the dioxygenase DcmC. In this study, the overall DCM degradation pathway of the consortium L1 was proposed and, particularly, the lower part on the DCP degradation was characterized at the genetic and biochemical levels.